2021
DOI: 10.30773/pi.2020.0201
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumoral Presentation of Cerebral Amyloid-Beta Angiopathy: Case Report and Review of Literature

Abstract: Objective Cerebral amyloid angiopathy-related inflammation (CAA-RI) is a rare and potentially treatable encephalopathy that usually affects people older than 50 years old and has an acute or subacute clinical presentation characterized by rapidly evolving cognitive decline, focal deficits and seizures. In a small subset of patients the disease can adopt a pseudotumoral form in the neuroimages that represents a very difficult diagnostic challenge. Methods Here in we report a patient with a tumour-like presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Intrathecal production of these antibodies was demonstrated, and antibody titers have been shown to decrease after steroid therapy. 11 59 60 61 62 Piazza et al 60 found that antibody titers tend to be correlated with clinical and imaging findings. These autoantibodies could potentially serve as biomarkers for iCAA in the future, which would discriminate this condition from noninflammatory CAA or from other neuroinflammatory disorders and even help in monitoring the treatment response, although further studies are needed to confirm this.…”
Section: Pathology and Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…Intrathecal production of these antibodies was demonstrated, and antibody titers have been shown to decrease after steroid therapy. 11 59 60 61 62 Piazza et al 60 found that antibody titers tend to be correlated with clinical and imaging findings. These autoantibodies could potentially serve as biomarkers for iCAA in the future, which would discriminate this condition from noninflammatory CAA or from other neuroinflammatory disorders and even help in monitoring the treatment response, although further studies are needed to confirm this.…”
Section: Pathology and Pathogenesismentioning
confidence: 99%
“… 36 Three-quarters of patients presented with acute or subacute encephalopathy with or without focal neurological signs (46%–58%) and headache (22%–41%), with seizures in one-third. 8 11 14 23 24 27 29 30 31 36 37 39 54 80 83 Constitutional symptoms are often absent, although patients may complain of dizziness or nausea. 3 Immune-mediated vascular function changes are believed to be responsible for iCAA symptoms, and induce relatively rapid cognitive and/or functional decline over weeks to months, which are factors in the differential diagnosis for rapidly progressing dementia syndrome.…”
Section: Clinical and Laboratory Featuresmentioning
confidence: 99%
See 3 more Smart Citations